BRODUT: Adaptasi Musik Dangdut dalam Kesenian Kubro Siswo di Dusun Gunung Lemah Kabupaten Magelang - Aditya, Bonggan; Muttaqin, Mohammad (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This research examines the phenomenon of dangdut music adaptation within the traditional art form of Kubro Siswo in Gunung Lemah Hamlet, Magelang Regency, now known as "BRODUT" or Kubro Dangdut. The study's objective is to identify the forms of dangdut music adaptation implemented in Kubro Siswo art, driven by the challenge traditional arts face in maintaining relevance amidst modernization and changing public tastes. Employing a qualitative musicological approach to allow for in-depth analysis of the music within a community's folk songs, data was collected through observation, structured and unstructured interviews with the chairman and music arranger of New Argo Mudo, and documentation. The findings reveal that the New Argo Mudo Art Group successfully adapted dangdut music by incorporating modern instruments like electric guitar, bass, keyboard/organ, drums, dangdut flute, and ketipung, without abandoning Kubro Siswo's original principles. This adaptation led to changes in the patterns, rhythms, and melodies of the performance, creating a distinctive dangdut groove with richer melodic and harmonic variations, thus making the performances more dynamic and engaging. Ultimately, this research concludes that with creativity and appropriate adaptation, traditional arts can continue to thrive and remain relevant through evolving times.